Practice versus theory - is there competition between academic and vocational qualifications? : Empirical results from the German labor market - Annen, Silvia [Verfasser]; Hufnagl, Julia [Verfasser]; Tiemann, Michael [Verfasser] (My University, 2025)
“This chapter contributes to the global debate on the relevance of academic versus vocational qualifications for individuals and enterprises by focusing on the usability of vocational and academic qualifications in the German labor market. Rational choice theory, human capital theory, and segmentation theory try to explain matching processes and recruiting decisions in the labor market and, therefore, form the theoretical background. To evaluate individual labor market outcomes, we calculated Ordinary Least Sqares (OLS)-regression models containing variables associated with a positive effect on income and variables representing the individuals’ rationales, their socioeconomic background and types of qualification, and enterprises’ characteristics. We used data from the German employment survey of 2018 and its follow-up survey of 2019. Our results show differences in qualification paths and perceptions of competition between vocational and academic skills across industry sectors. Regarding labor market utilization, our analyses show that individual variables explain less variance of income than macro variables. For individuals, labor market usability is a very relevant aspect of their educational choices in vocational education, training, and higher education. At the same time, personal career aspirations and socio-demographic background have a minimal impact on individual income. Rather, sector and company size largely determines individual income.” (authors’ abstract; BIBB-Doku)
Keywords: G 1.2.3.1 Potenziale; G 1.3.3.1 Qualifikationsverwertung; 370; Bildungsabschluss; Studienabschluss; Berufsabschluss; Qualifikationsniveau; Qualifikationsverwertung; Einflussfaktor